Ongoing censorship regime (Russia) - Voidly (2025)
CRITICAL severity censorship detected in Russia. Confidence: 92%. Data sourced from OONI.
Censorship Incident ID: RU-2025-0009
Keywords: censorship; RU; censorship; critical